Between Air and Electricity: Microphones and Loudspeakers as Musical Instruments - Eck, Cathy van (New York Bloomsbury Academic, 2017)
Composers and sound artists have explored for decades how to transform microphones and loudspeakers from inaudible technology into genuinely new musical instruments. While the sound reproduction industry had claimed perfect high fidelity already at the beginning of the twentieth century, these artists found surprising ways of use - for instance tweaking microphones, swinging loudspeakers furiously around, ditching microphones in all kinds of vessels, or strapping loudspeakers to body parts of the audience. Between air and electricity traces their quest and sets forward a new theoretical framework, providing historic background on technological and artistic development, and diagrams of concert and performance set-ups. From popular noise musician Merzbow to minimalist classic Alvin Lucier, cult instrument inventor Hugh Davies, or contemporary visual artist Lynn Pook - they all aimed to make audible what was supposed to remain silent.